Method of overall resource efficiency measure of MIMO wireless communications - Jin-zhu LIU; Lian-feng SHEN (Tongxin xuebao)
A general mode of overall resource efficiency measure of communication systems is proposed.Based on it,the specific method of overall resource efficiency measure of multiple input multiple output (MIMO) wireless communica-tion systems is presented.The theory analysis and practice measure results show that although the requirements of the normalized bandwidth and the normalized signal noise ratio (SNR) of MIMO systems are relatively small due to the utilization of the space resource,but the overall resource efficiencies of the existing MIMO systems are low,and the gaps between their performances and their potential capacities are large,when compared to that of the existing communication systems under the basic additive white Gaussian noise (AWGN) channel.